Development of a green ict model for sustainable enterprise strategy - Anthony Junior, Bokolo; Mazlina, Abdul Majid (Penerbit UTM Press, 2016)
Enterprise energy consumption is expected to increase enterprise costs and CO2 emissions. Presently ICT is seen as an enabler to resolve high energy, cost issues and bring greater efficiency. This is referred as Green ICT which involves energy conservation and cost reduction of ICT usage. Various countries have already applied Green ICT initiatives to reduce CO2 emissions. Greening ICT strategies in enterprise can decrease these negative impacts. Thus Green ICT aimed at influencing not only technology but also competitive strategy and even the legitimacy of some business strategic options in enterprise. Current findings suggest that although ICT Professionals are already concerns about climate change and power consumption of ICT, there is still a lack of a model that can reduce the time taken to implement Green strategies in enhancing business value in enterprise. Therefore this paper utilized secondary research by reviewing literature on Green ICT and developed a Green ICT model for sustainable enterprise strategy, aimed at reducing time taken to initiate and diffuse Green strategies for enhancing business value in enterprise. The research implication for future studies involves the evaluation of the Green ICT Model. The evaluation will be done using Structural Equation Modelling (SEM) to test the hypothesis derived from the literatures and to check the correlation among the independent, control and dependent variables in this research paper.